2021
DOI: 10.1111/and.14174
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐622 acts as a tumor suppressor to induce cell apoptosis and inhibit metastasis in human prostate cancer

Abstract: Growing evidence indicating the critical modulator roles of microRNAs (miRNAs) involved in prostate cancer (PCa) metastasis that holds great promise as therapeutic targets. Herein, we transfected the miR‐622 mimic into PC3 cells and evaluated the effects of this interference on these tumour cells' growth and the expression of specific metastatic genes. Transfecting of miR‐622 mimic and inhibitor, negative control (NC) inhibitor and NC was established using Lipofectamine 2000. The mRNA levels of miR‐622 and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…37 miR-622 Open access also demonstrated as a tumor suppressor in some other human tumors, such as CRC, glioma, prostate cancer and renal cell carcinoma. [38][39][40][41] As a result, these data indicated that circ-0000512 knockdown might weaken TNBC progression and immune escape by promoting PD-L1 ubiquitination through sponging the miR-622/CMTM6 axis.…”
Section: Discussionmentioning
confidence: 79%
“…37 miR-622 Open access also demonstrated as a tumor suppressor in some other human tumors, such as CRC, glioma, prostate cancer and renal cell carcinoma. [38][39][40][41] As a result, these data indicated that circ-0000512 knockdown might weaken TNBC progression and immune escape by promoting PD-L1 ubiquitination through sponging the miR-622/CMTM6 axis.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, some patients suffer chemotherapy resistance, which, in some instances, is elucidated as tumor recurrence or progression [ 22 24 ]. It is essential to discern between two types of resistance: acquired and internal resistance [ 25 27 ]. Internal resistance is inherent as resistant cells exist within the tumor before initiating therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miRNAs have demonstrated predictive solid biomarker potential in PCa, and the dysregulation of these miRNA expressions is a hallmark of neoplasia formation and progression [14]. Though numerous miRNAs, such as miR-20b, miR-30, miR-32, miR-34, miR-199b, miR-210, miR-532, and miR-622 have been established to encourage or repress metastasis in PCa, many other miRNAs that play critical regulatory roles in metastasis have not yet been discovered [15][16][17][18][19][20]. MiR-32 is an intronic miRNA located in intron 14 of c9orf5, the gene encoding transmembrane protein 245 (TMEM245), on chromosome 9.…”
Section: Discussionmentioning
confidence: 99%